2020
DOI: 10.1109/access.2020.3031019
|View full text |Cite
|
Sign up to set email alerts
|

OpenSHC: A Versatile Multilegged Robot Controller

Abstract: Multilegged robots have the ability to perform stable locomotion on relatively rough terrain. However, the complexity of legged robots over wheeled or tracked robots make them difficult to control. This paper presents OpenSHC (Open-source Syropod High-level Controller), a versatile high-level controller capable of generating gaits and poses for quasi-static multilegged robots, both simulated and with real hardware implementations. With full Robot Operating System (ROS) integration, the controller can be quickl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Among a wide range of control approaches, foothold adaptation based on online force estimation using direct measurements of the joint forces by dedicated sensors [42], [49]- [51], or based on the estimation of joint torques using servomotors current readings [45], [52] are utilized in existing solutions. However, in our design choices, we have been limited to the usage of the Dynamixel AX-12A servomotors that do not directly provide the information about the motor current, and thus the joint torque.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Among a wide range of control approaches, foothold adaptation based on online force estimation using direct measurements of the joint forces by dedicated sensors [42], [49]- [51], or based on the estimation of joint torques using servomotors current readings [45], [52] are utilized in existing solutions. However, in our design choices, we have been limited to the usage of the Dynamixel AX-12A servomotors that do not directly provide the information about the motor current, and thus the joint torque.…”
Section: Related Workmentioning
confidence: 99%
“…Hence, given the control cycle period T con there are n sp = t g n −1 gp T −1 con individual poses on the path between g p l curr and g p l new . We have selected the positive amplitude of the sine wave as the desired leg path for its smooth profile, although more elaborated swing path can be designed considering the leg dynamics and terrain characteristics, e.g., as in [25], [52], [59]; however, such a trajectory optimization requires exteroceptive sensing and is out of the scope of the presented design of the HAntR. Hence, the immediate foottip pose g p l at the control cycle k is computed as…”
Section: Algorithm 1: Gait Cycle Executionmentioning
confidence: 99%
“…They demonstrated that a series-elastic actuated hexapod robt climbed over different obstacles. Tam et al with CSIRO's Robotics and Autonomous Systems Group developed Opensource Syropod High-level Controller (OpenSHC) which is a controller for multilegged robots to generate statically stable gaits [19]. For a hexapod robot, Belter and Skrzypczyński [20] developed feasible gait patterns using evolutionary algorithm with dependencies inspired by typical insect behaviour.…”
Section: Introductionmentioning
confidence: 99%